Studi Komparasi Organizational Attractiveness Ditinjau Dari Job-Security - Wildanurdiya Istiq’ma, Isrofi; Handoyo, Seger (Jurnal Syntax Fusion, 2023)
The COVID-19 pandemic that caused many people to lose their jobs due to layoffs has made current candidates reconsider job-security as something they look for when looking for a job. Previous research shows that job-security has a significant effect on organizational attractiveness, but there are still inconsistencies in research results. This study aims to determine the effect of job-security on organizational attractiveness, as well as to determine the difference in the effect of offering and not offering job-security by the company. The study used a quantitative approach with data collection techniques using the survey method. Job-security is operated as a manipulation by referring to the characteristics of Lievens et al (2005) and divided into 2, namely companies that offer job-security and companies that do not offer job-security. Organizational attractiveness was measured using a scale from Aiman-Smith et al (2001). The number of participants was 241 people. The data analysis technique used was repeated measure analysis of variance. The results in this study show that job-security has a significant effect on organizational attractiveness, and it was found that the effect of companies that offer job-security was found to be greater than companies that do not offer job-security.